2011
DOI: 10.18388/abp.2011_2218
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of dehydroepiandrosterone (DHEA) in rat model of Alzheimer's disease.

Abstract: The current study was undertaken to elucidate a possible neuroprotective role of dehydroepiandrosterone (DHEA) against the development of Alzheimer's disease in experimental rat model. Alzheimer's disease was produced in young female ovariectomized rats by intraperitoneal administration of AlCl(3) (4.2 mg/kg body weight) daily for 12 weeks. Half of these animals also received orally DHEA (250 mg/kg body weight, three times weekly) for 18 weeks. Control groups of animals received either DHAE alone, or no DHEA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 56 publications
5
37
1
1
Order By: Relevance
“…2I). These results are in agreement with Morinaga et al [66] who demonstrated that steroids exerts antiamyloidogenic activity, and Aly et al [67] who observed that dehydroepiandrosterone (DHEA) can protect against Ab toxicity in hippocampal cells.…”
Section: Histopathology Assaysupporting
confidence: 91%
“…2I). These results are in agreement with Morinaga et al [66] who demonstrated that steroids exerts antiamyloidogenic activity, and Aly et al [67] who observed that dehydroepiandrosterone (DHEA) can protect against Ab toxicity in hippocampal cells.…”
Section: Histopathology Assaysupporting
confidence: 91%
“…Aly et al 32 reported that BDNF levels were significantly reduced in rat model of AD induced by intraperitoneal administration of aluminum chloride (AlCl 3 ), while Kirk et al 33 reported that changes in serum level of BDNF might be contributing to shrinkage of the hippocampus that is associated with age related memory decline in late adulthood. Moreover, it was found that a novel polymorphism in BDNF gene was associated with late onset AD.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum is not very toxic at normal levels, but its chronic exposure may lead to speech disturbance, dyspraxia, tremors, psychosis, partial paralysis, loss of memory and cognition, and ultimately death (Buraimoh et al 2012). Aluminum accumulates in the hippocampus in the forms of amyloid beta plaques and neurofibrillary tangles which underlie the pathogenesis of AD (Aly et al 2011). Accumulation of aluminum results in reactive oxygen species (ROS) formation which depletes normal antioxidant defense mechanism followed by oxidative stress and lipid peroxidation leading to amyloid deposition (Oguz et al 2012).…”
Section: Introductionmentioning
confidence: 99%